Influência das características físico-químicas dos solos no ciclo hidrobiogeoquímico do mercúrio na região do Rio Aracá - AM - Oliveira, Luciana Camargo de; Botero, Wander Gustavo; Santos, Ademir dos [UNESP]; Cordovil, Mirela Cristina de Oliveira [UNESP]; Rocha, Julio Cesar [UNESP]; Silva, Heliandro Cordovil da (Sociedade Brasileira de Química, 2011)
The region of Aracá River (Middle and Upper Rio Negro-AM) has peculiar characteristics, having soils with atypical profile and high organic matter contents in great deep. The levels of aluminum and iron in the soil samples increased as a function of depth and concentrations of mercury ranged from 0.097 to 0.964 µg g-1. Statistical analysis showed the degree of similarity between soil samples collected. The highest concentrations of mercury in soil samples are directly related to soil higher content of organic matter, directly influencing the fate and bioavailability of mercury species to the environment.
Influence of physical and chemical characteristics of soils in the hydrobiogeochemical cycle of mercury in the Rio Aracá - AM
Keywords: soil; mercury; Aracá - AM River